An Analysis of EFL Students’ Perceptions of Learning Difficulties in Digital Learning - Radha Sulistia Gultom; Taufik Suadiyatno; Edi Firman (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
The rapid integration of digital learning in higher education has transformed the landscape of language learning, presenting unique challenges for students of English as a Foreign Language (EFL). This study aims to analyze the perceptions of eighth-semester EFL students regarding the learning difficulties they face in a digital environment while taking English-based courses. Using a descriptive qualitative design, this study employed a dichotomous-scale screening questionnaire distributed to 12 respondents, followed by semi-structured interviews with six key informants selected through purposive sampling. The findings of the quantitative analysis indicate that participants experienced difficulties in communicating with their lecturers, with 91.7% experiencing problems with an inconsistent internet connection, and 91.7% reporting a decline in concentration and motivation. From a qualitative perspective, thematic analysis categorised these challenges into five main categories: technological infrastructure failures; boredom with the largely one-way nature of the learning process in the form of online lectures; mental fatigue due to excessive digital workload and anxiety; social isolation resulting from the lack of a tangible academic community; and language barriers arising from limited opportunities to speak and a fear of making mistakes. When evaluated through Krashen’s Affective Filter Theory, Moore’s Transactional Distance, and Vygotsky’s Sociocultural Theory, the findings of this study demonstrate how physical separation and rigid online systems contribute to a significant increase in the affective filter and transactional distance, which in turn hinders the effective development of English language skills. This study provides actionable recommendations for educational institutions and teachers on creating engaging, supportive and flexible digital language learning environments.